Improve Push Skills in Hockey Games Through Games Based Approach - Syahruddin (Journal of Physical and Outdoor Education, 2023)
The purpose of this study was to determine the effect of Games Based Approach (GBD) on hockey push skills. The research method used is an experimental method with a one group pretest-posttest design. The population in this study were students consisting of 69 people using a random sampling technique. The instrument used is the hockey test push. Data processing was carried out using the paired sample T-test method in the SPSS version 23 application. The results of the data analysis using the paired sample test showed that a mean of 24.375 was obtained, which means that there was a difference in the score from the pretest posttest in the hockey ball push skill. In addition, statistical data shows a statistical price of t = 58.541, with df = 68, and a significant figure or p-value = 0.000 <0.05. Thus learning the game based approach (GBA) has a significant influence on improving push skills in hockey games